Advancing Legal Education in Pakistan through Online Dispute Resolution: Opportunities and Challenges in Clinical Legal Education - Arshad Nawaz Khan,; Dr. Bahadar Ali,; Mubashir Ahmad, (Journal of Peace, Development and Communication, 2023)
The legal profession in Pakistan has traditionally been hesitant to embrace new technologies, including online dispute resolution (ODR) mechanisms. Despite the potential benefits of ODR in terms of enhancing access to justice through university legal aid clinics, the adoption of these mechanisms has been slow. To address this issue, a qualitative case study has been conducted to explore the opportunities and challenges associated with using ODR in clinical legal education in Pakistan. This study employs an interpretivist research philosophy and a qualitative approach, utilizing in-depth interviews with various stakeholders, including law faculty, lawyers, ADR practitioners, judges, students, and litigants. The data collected from the interviews and survey has been analyzed using thematic analysis. Ethical principles and guidelines have been strictly followed throughout the study, and the time horizon is cross-sectional. To provide a theoretical framework for the study, the Technology Acceptance Model (TAM) and the Diffusion of Innovations Theory have been used. These theories helped to identify the factors that influence the acceptance and diffusion of ODR in Legal Aid Clinics run by universities. By examining these factors, the study aims to contribute to the development of a more technologically advanced University Legal aid system in Pakistan and to inform the integration of ODR mechanisms into the legal education curriculum. The study's findings will have important implications for legal education and the practice of law in Pakistan. Furthermore, the research will contribute to the growing body of knowledge on ODR mechanisms in the legal clinics, informing the development of policies and practices aimed at improving access to justice in Pakistan. This study has significant potential to enhance the global discourse on the potential of ODR mechanisms to improve access to justice and to contribute to the development of more technologically advanced legal systems around the world.